Satralizumab as an add-on treatment in refractory pediatric AQP4-antibody-positive neuromyelitis optica spectrum disorder: a case report - Li, Xiaojing; Wu, Wenlin; Zeng, Yiru; Wu, Wenxiao; Hou, Chi; Zhu, Haixia; Liao, Yinting; Tian, Yang; Chen, Zongzong; Peng, Bingwei; Chen, Wen-Xiong (Frontiers in Immunology, 2023)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune disease of the central nervous system. Relapse and incomplete recovery from relapse are common in NMOSD. Most patients with NMOSD have IgG to aquaporin-4 (AQP4-IgG). New biological agents for AQP4-IgG-seropositive NMOSD, such as satralizumab, have become available for maintenance therapy. Satralizumab is an anti-interleukin-6 receptor monoclonal antibody. To date, few studies have evaluated satralizumab as an add-on treatment in pediatric NMOSD patients. Here, we report an 11-year-old girl with NMOSD who frequently relapsed under long-term treatment, including oral prednisone, rituximab, mycophenolate mofetil (MMF), and maintenance intravenous immunoglobulin treatment even with B-cell depletion. For the poor treatment response and to improve the efficacy of relapse prevention further, the patient received satralizumab treatment as an add-on therapy to MMF plus oral prednisone, with a dose of 120 mg administered subcutaneously at weeks 0, 2, and 4 and every 4 weeks after that. After initiating satralizumab, the patient remained relapse-free for 14 months at the last follow-up. Satralizumab might be effective and safe as an add-on treatment in refractory pediatric AQP4-IgG-seropositive NMOSD under B-cell depletion.